Students’ Perception of The Use of Code Mixing by Student Teacher - Pramatya Sukarno Putri; Ahdi Riyono; Rismiyanto (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2023)
Code mixing is one of teaching strategy. However, for some levels of students, the teacher has to take control of the use of code mixing in class in order that students can get the target language. This research aims to discover the students’ perceptions of the use of code mixing by student teacher in English class. This research involved 36 students of the tenth grade of SMAN 1 Kudus in academic year 2022/2023 through questionnaire submission and 6 students through interview. The result of this research showed that the students had positive perception in cognitive, affective, conative, and also the strengths and weaknesses aspects. The use of code mixing can give a good impact on upgrading the students’ ability in English learning and increase the students’ knowledge. On the other side, the weaknesses of code mixing used by the student teacher were making students unfamiliar with the use of English phrases which can affect their English skills. This study expects the teacher considers code-mixing as teaching strategy so the students can get their target language and have no difficulties understanding the materials.